Assessment of CA-125 levels and imaging findings in women with suspected malignant ovarian tumors - Elora, Ashfi Laila; Kader, Mousumi; Chowdhury, Mina; Amin, Rogina; Afrose, Taslima; Jolly, Rabeya Sultana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ovarian cancer diagnosis is growing due to the prudent use of investigational methods. Imaging techniques and molecular biomarkers are the commonly used. A correct ovarian cancer staging assists gynecological oncologists in determining whether the patient required primary debulking surgery or neoadjuvant chemotherapy. The aim of the study was to evaluate the accuracy of CA-125 titre, USG of whole abdomen imaging and CT scan for diagnosis of ovarian malignancy. Methods: A prospective, observational study was conducted Gynae Oncology Unit, Department of Obs and Gynae, Dhaka Medical College Hospital, Dhaka during January 2022 to December 2022. Total 96 patients who were diagnosed clinically as malignant ovarian tumor were included in the study. Results: The sensitivity of malignant ovarian tumors by USG was calculated to be 89.4%, specificity was 76.7%, accuracy was 85.4%, PPV was 89.4%, and NPV was 76.7%. The validity of CA-125 in malignant ovarian tumors was demonstrated by calculating sensitivity of 75.8%, specificity of 90.0%, accuracy of 80.2%, PPV of 94.3%, and NPV of 62.8%. The sensitivity of malignant ovarian tumors by CT was calculated to be 90.9%, specificity was 86.7%, accuracy was 89.6%, PPV was 93.8%, and NPV was 81.3%. Using histology as the gold standard. Conclusion: The results of this study demonstrate the superior diagnostic capabilities of two distinct imaging modalities (USG and CT) in determining the degree of malignant spread.